Influência do micro-habitat e da distribuição espacial de recursos na amostragem de besouros escarabeíneos - Silva, Július César Cerqueira (2017)
The increasing concern on the negative impacts resulting of anthropogenic actions on biodiversity has made necessary to improve the biodiversity monitoring research in different habitats. In order to understand ecosystem functioning, processes and the species/environment interactions, researchers often use biological indicators. The individuals of the subfamily Scarabeinae, popularly known as dung beetles, are widely used as ecological indicators in researches focused on biodiversity and conservation. However, the results of these studies may be influenced by the spatial structure in environmental factors and resource availability, biasing or misleading results. Thus, this work aimed to verify the influence of microhabitat heterogeneity and the spatial distribution of food resources on dung beetles sampling. I carried the study out at the Estação Ecologica do Jari, in areas of primary Amazon Rain Forest. We set up fifty sampling points with a minimum distance of 250 meters between them. Prior to sampling a dung pile was placed near each sampling point, at distances ranging from 1 to 100 meters, in order to simulate a spatial structure of "natural" dung piles. We also left 10 sampling points without external fecal deposit, which were considered control treatment. At each sampling point a pitfall trap with attractive bait was installed, left in the field for 48 hours. In each of the sampling points we obtained the following microhabitat variables: canopy openness, litter weight, above-ground vegetation biomass, soil compaction and elevation. We found that the canopy openness was the most important microhabitat variable, negatively affecting community structure of dung beetles. The above-ground biomass and soil compaction showed a significant effect on equitability, with positive and negative effects, respectively. The litter weight positively affected the average biomass of beetles collected in the samples. Even in natural environments without a significant anthropogenic impact, dung beetles are affected by microhabitat factors, being sensitive to small environmental variations that directly affect the community structure. The spatial distribution of food resources greatly influences the structure of the sampled community. This influence may lead to bias in the results obtained and possibly in the conclusions of studies using dung beetles as an indicator group of disturbances.